Nufenoxole, a new antidiarrhoeal agent, inhibits fluid secretion in the human jejunum. Issue 1 (January 1985) - Moriarty, K J; Rolston, D D; Kelly, M J; Shield, M; Clark, M L
Abstract : Nufenoxole is an orally active antidiarrhoeal agent which binds to opioid receptors in the brain and myenteric plexus of the intestine. A perfusion technique has been used to investigate the effect of nufenoxole (1 mg/kg intrajejunally) on water and solute transport stimulated by the secretagogue, dioctyl sodium sulphosuccinate, in the human jejunum in vivo. Nufenoxole reversed the direction of jejunal transport of salt and water from net secretion to net absorption. These changes in water and electrolyte transport were inhibited by intravenous naloxone, the opioid antagonist. Nufenoxole possesses potent antisecretory properties, which are mediated via opioid receptors and may contribute to its antidiarrhoeal action in man.